The ALPK1 pathway drives the inflammatory response to Campylobacter jejuni in human intestinal epithelial cells. - Jiannan Cui (Public Library of Science (PLoS), 2021)
The Gram-negative bacterium Campylobacter jejuni is a major cause of foodborne disease in humans. After infection, C. jejuni rapidly colonizes the mucus layer of the small and large intestine and induces a potent pro-inflammatory response characterized by the production of a large repertoire of cytokines, chemokines, and innate effector molecules, resulting in (bloody) diarrhea. The virulence mechanisms by which C. jejuni causes this intestinal response are still largely unknown. Here we show that C. jejuni releases a potent pro-inflammatory compound into its environment, which activates an NF-κB-mediated pro-inflammatory response including the induction of CXCL8, CXCL2, TNFAIP2 and PTGS2. This response was dependent on a functional ALPK1 receptor and independent of Toll-like Receptor and Nod-like Receptor signaling. Chemical characterization, inactivation of the heptose-biosynthesis pathway by the deletion of the hldE gene and in vitro engineering identified the released factor as the LOS-intermediate ADP-heptose and/or related heptose phosphates. During C. jejuni infection of intestinal cells, the ALPK1-NF-κB axis was potently activated by released heptose metabolites without the need for a type III or type IV injection machinery. Our results classify ADP-heptose and/or related heptose phosphates as a major virulence factor of C. jejuni that may play an important role during Campylobacter infection in humans.